FOREST unbiased Galactic plane imaging survey with the Nobeyama 45 m telescope (FUGIN). VI. Dense gas and mini-starbursts in the W 43 giant molecular cloud complex. (22nd May 2020) - Kohno, Mikito; Tachihara, Kengo; Torii, Kazufumi; Fujita, Shinji; Nishimura, Atsushi; Kuno, Nario; Umemoto, Tomofumi; Minamidani, Tetsuhiro; Matsuo, Mitsuhiro; Kiridoshi, Ryosuke; Tokuda, Kazuki; Hanaoka, Misaki; et al.
Abstract: We performed new large-scale 12 CO, 13 CO, and C 18 O J = 1–0 observations of the W 43 giant molecular cloud complex in the tangential direction of the Scutum arm ( l ∼30°) as a part of the FUGIN project. The low-density gas traced by 12 CO is distributed over 150 pc × 100 pc ( l × b ), and has a large velocity dispersion (20–30 km s −1 ). However, the dense gas traced by C 18 O is localized in the W 43 Main, G30.5, and W 43 South (G29.96−0.02) high-mass star-forming regions in the W 43 giant molecular cloud (GMC) complex, which have clumpy structures. We found at least two clouds with a velocity difference of ∼10–20 km s −1, both of which are likely to be physically associated with these high-mass star-forming regions based on the results of high 13 CO J = 3–2 to J = 1–0 intensity ratio and morphological correspondence with the infrared dust emission. The velocity separation of these clouds in W 43 Main, G30.5, and W 43 South is too large for each cloud to be gravitationally bound. We also revealed that the dense gas in the W 43 GMC has a high local column density, while "the current SFE" (star formation efficiency) of the entire GMC is low ($\sim\!\! 4%$ ) compared with the W 51 and M 17 GMC. We argue that the supersonic cloud–cloud collision hypothesis can explain the origin of the local mini-starbursts and dense gas formation in the W 43 GMC complex.